Športna rekreacija invalidov - osrednja tema 13. Kongresa športa za vse - Berčič, Herman (Šport (Ljubljana), 2019)
The last 13th Sport for All Congress (2018) was dedicated to disability sport and recreation. Given the structure and complexity of the disability issue, the main topic of the congress was discussed from several points of view. Various experts presented their contributions that delved into sport & recreation of disabled people in medicinal, kinesiological and sociological terms. Medical experts presented the basic knowledge about individual types of disabilities and disabled people%s possibilities to engage in specific sports or physical activities. The kinesiological contributions discussed integration of different groups of disabled people into sport and recreational activities that can significantly improve the quality of life of functionally challenged people and those with impaired mobility. The sociological set of contributions was dedicated to individual social models of integrating disabled people into the world of physical and sports activities. Examples of good practice added to the success of the congress.
Keywords: congress; diabled people; invalidi; kineziološki vidik; medicinski vidik; sociološki vidik; sport; sport for all; šport; športna rekreacija